1975
DOI: 10.1111/j.1365-2621.1975.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

An equation for correlating equilibrium moisture content in foods

Abstract: The object of this study was to show that a multilayer adsorption equation, originally developed for physical adsorption on nonuniform surfaces, can be used to describe reasonably well the water sorption isotherms of a great variety of foods and food components. Apparently, the proposed equation has not been applied to the food area before.Characteristics parameters of the adsorption equation for each of the foods tested were computed and a statistical analysis of its applicability was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 21 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…An analytical expression for the isotherm is also required for the quantitative analysis of storage stability (Karel, Mizrahi & Labuza, 1971;Labuza, Mizrahi & Karel, 1972). Iglesias et al, 1975a) showed that a multilayer adsorption equation, originally developed by Halsey (1948) could be used to describe the water sorption behaviour of a great variety of foods. The sorption data on beef were treated according to the Halsey's equation as used by Iglesias et al (1975a) andChirife (1976~) : In lnfio&= -r In X + In u"…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analytical expression for the isotherm is also required for the quantitative analysis of storage stability (Karel, Mizrahi & Labuza, 1971;Labuza, Mizrahi & Karel, 1972). Iglesias et al, 1975a) showed that a multilayer adsorption equation, originally developed by Halsey (1948) could be used to describe the water sorption behaviour of a great variety of foods. The sorption data on beef were treated according to the Halsey's equation as used by Iglesias et al (1975a) andChirife (1976~) : In lnfio&= -r In X + In u"…”
Section: Resultsmentioning
confidence: 99%
“…An attempt was also made to describe the various experimental sorption isotherms using a multilayer adsorption equation developed by Halsey (1948) and recently shown by Iglesias, Chirife & Lombardi (1975a) to describe the water sorption behaviour of several foods.…”
Section: Introductionmentioning
confidence: 99%
“…e Hasley model is recommended for use for the study of the sorption isotherms of meats, milk products, and vegetables [35]. Iglesias et al [36] applied the Hasley model to describe reasonably the sorption of dried figs, apricots, and raisins. Moreover, in 1985, Lomauro et al [29] successfully used this model to study the water sorption of several nuts and oil seeds.…”
Section: Fitting Of Sorption Isotherm Models To Experimentalmentioning
confidence: 99%
“…Six food products, of which desorption isotherms at various temperatures (three or more) are available in the literature, were used for our analysis. These were thyme, aniseed, marjoram and fennel (Wolf, Spiess & Jung, 1973), wheat kernel (Day & Nelson, 1965) and sugar beet root (Iglesias et al, 1975). The equilibrium data of the first five products were analysed according to the BET equation:…”
Section: Estimation Of the Bet Heat Of Desorptionmentioning
confidence: 99%